FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN INISIASI MENYUSU DINI (IMD) DI KABUPATEN BANTUL - Lutfiyati, Afi; Haryanti, Fitri; Lusmilasari, Lely (Media Ilmu Kesehatan, 2017)
Background: Early initiation of breastfeeding can reduce the infants mortality under the age of 28 days and can affect exclusive breastfeeding process (Roesli, 2010). In early initiation of breastfeeding and exclusive breastfeeding, there is disparities of each health center in Bantul district. Objective: The aim of this study was to identify the association between maternal education, maternal occupation, place of childbirth, birth attendant, and health provider’s support with early initiation of breastfeeding. Methods: The study was conducted from March 23 to April 13, 2014, used crossectional design. Subjects were the entire breastfeeding mothers with infants aged 6-8 months who meet the inclusion and exclusion criteria (204 samples). Sampling with consecutive tecnique. Data obtained from secondary data and questionnaires. Data Analysis with SPSS using Chi-square test. Results: In bivariate analysis, there was no statistically and clinically significant association between maternal education with early initiation of breastfeeding p=0.882; OR=0.9; 95% CI=0.44 to 2.03, maternal occupation  p=0.463 : OR=1.3 : 95% CI=0.65 to 2.59 , and birth attendant p=0.211 : OR=4.8 : 95% CI=3.69 to 6.33. Other factors that have a statistically and clinically significant association with early initiation of breastfeeding is the place of childbitrh p=0.007 OR=16.4; 95% CI=1.78 to 150.96 and health provider’s supports p=0.001 : OR=4.4 : 95% CI=2.03 to 9.68. Conclusions and suggestions: There is statistically and clinically significant association between place of childbirth and health provider’s supports with early initiation of breastfeeding. Further research is expected involving the variable support of her husband/family with a prospective cohort to examine the association between early initiation of breastfeeding with exclusive breastfeeding. Keywords: Early Initiation of Breastfeeding, maternal education, maternal occupation, birth attendant, place of childbirth, health provider’s supports.